Irrotational Approximation to Steady Supersonic Flow in Two Space Variables (Journal of Partial Differential Equations, 2008)
" On the assumption that the total variation of the initial data is suffi- ciently small, we can use the stability results of Dafermos to get the L2 estimate of the difference between the solutions to the isentropic steady Euler system and the potential flow equations with the same initial data."
Keywords: Irrotational approximation; supersonic flow; steady Euler system